DevOps troubleshooting for Linux Server : is the server down? : tracking down the source of network problems - Rankin, Kyle (Addison-Wesley Professional, 2012)
No matter where you fit in a DevOps organization, network troubleshooting skills are invaluable. It can be difficult to track down networking problems, sometimes because they often impact a system in strange ways. In this digital short, Kyle Rankin walks you through how to isolate and diagnose a network problem step-by-step by testing problems on different network layers. He also lays the groundwork for troubleshooting techniques for specific network services (such as DNS). This digital short is an adapted excerpt from DevOps Troubleshooting: Linux Server Best Practices (isbn 9780321832047) by Kyle Rankin. The content of this digital short may differ from the content in the book. Purchasers of this digital short are invited to use a coupon code good for 25% off the list price of the book on InformIT exclusively.